Uterine artery embolization : a systematic review of the literature and proposal for research - Broder, Michael S.; Harris, Katherine M.; Morton, Sally C.; Sherbourne, Cathy Donald; Brook, Robert H. (Robert Henry), 1943-; Rand Corporation; RAND Health (Santa Monica, CA : RAND, 1999)
The benign tumors known as uterine leiomyomata are a common cause of significant, often disabling symptoms among women. For women whose symptoms are not controlled by hormones or nonsteroidal anti-inflammatory drugs, surgery--hysterectomy or myomectomy--is required. Over the long term, about 10 percent of women who have had a myomectomy will later require hysterectomy to control bleeding. Uterine artery embolization (UAE) is a minimally invasive radiologic technique for reducing symptoms caused by uterine leiomyomata. A literature review revealed that the short-term results for UAE are roughly comparable with those for abdominal myomectomy, and the risks of UAE are similar to those of more-established procedures. Based on the recommendations of the ten-member expert panel convened to examine the literature review, the report concludes that the current data on UAE, while promising, are inadequate to recommend its use outside of clinical trials. A randomized, controlled trial with careful measurement of short- and long-term outcomes is crucial to establish the comparative risks and benefits of UAE, myomectomy, and hysterectomy. In addition, the panel recommended careful study of the costs of UAE and the establishment of a registry of patients undergoing UAE to provide nonexperimental data on the procedure.
"Health."
Includes bibliographical references (p. 39-42).
Also available on the internet via WWW in PDF format.
Keywords: Therapeutic embolization; Uterine fibroids -- Surgery; Uterus -- Blood-vessels -- Surgery; Uterus -- Tumors; Uterine Neoplasms